Tribunais de guerra : castigos e punições nas forças imperiais durante a campanha contra o Paraguai (1864-70) - Couto, Mateus de Oliveira (2016)
The War of the Triple Alliance against Paraguay (1864-70) was one of the largest armed conflict in southern America and represented the culmination of discussions between the countries involved - Argentina, Brazil and Uruguay against the Republic of Paraguay, about the borders and navigability on the river Plate estuary. During the war, the Army and the Imperial Navy were a mirror of slave society and landholding of the 19th century, especially when we look at crimes sentenced by the War Council; military offenses punished in the act; the sentences handed down by military courts, and especially the corporal punishment applied to squares, highlighting the pranchadas with sword and board for the lashes; treatment of official troops, in many cases, the behavior resembled the slave with its slave workers. The meaning of crimes shows that the squares of these weapons have not crossed his arms in front of abuse and arbitrariness dispensed by the commanders and the officers to subordinates. The vast majority of crimes and punishments applied to squares show that the environment in the Army and Navy was violent and tense and this climate of instability increased with the difficulties of the war, such as hunger and disease.